2021
DOI: 10.1097/shk.0000000000001860
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin-1β Alleviates Sepsis-Induced Skeletal Muscle Atrophy by Inhibiting Autophagy via AKT/mTOR Signaling Pathway in Rats

Abstract: Background: Several studies have shown that excessive protein degradation is a major cause of skeletal muscle atrophy induced by sepsis, and autophagy is the main pathway participating in protein degradation. However, the role of autophagy in sepsis is still controversial. Previously, we found that neuregulin-1b (NRG-1b) alleviated sepsis-induced diaphragm atrophy through the phosphatidylinositol-3 kinase signaling pathway. Akt/mechanistic target of rapamycin (mTOR) is a classic signaling pathway to regulate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…As reported, β2-agonist formoterol was reported to decrease protein degradation partially through inhibiting PI3K-AKT-mTOR mediated ALS, which prevented the muscle mass loss in fasted mice (118). Apart from that, the activation of PI3K-AKT signaling pathway prevented muscle atrophy via mTOR-mediated inhibition of ALS (119,120). Wang et al found that ghrelin ameliorated DOX-induced CMA by inhibiting excess autophagy via stimulating mTOR (62).…”
Section: Pi3k and Aktmentioning
confidence: 84%
“…As reported, β2-agonist formoterol was reported to decrease protein degradation partially through inhibiting PI3K-AKT-mTOR mediated ALS, which prevented the muscle mass loss in fasted mice (118). Apart from that, the activation of PI3K-AKT signaling pathway prevented muscle atrophy via mTOR-mediated inhibition of ALS (119,120). Wang et al found that ghrelin ameliorated DOX-induced CMA by inhibiting excess autophagy via stimulating mTOR (62).…”
Section: Pi3k and Aktmentioning
confidence: 84%
“…In previous studies, it has been demonstrated that GAS6/AXT and NRG signaling pathways play significant roles in modulating cellular behavior, such as tumor cell proliferation, tumor development, metastasis, and immunological infiltration. [53][54][55] In addition, it is seen that the communication between epithelial cells through cell-cell interactions is more pronounced in the cluster of NKAIN2 + EPI cells in the context of lymph node metastasis in OTSCC. This is evident in both the incoming and outgoing communication patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of muscle autophagy in critical illness has also been underscored. Although autophagy may contribute to critical illness induced muscle atrophy [44][45][46], its activation overall protects muscle function. In mice with hind-limb ischemia, autophagy inhibition indeed had a dual effect, diminishing muscle peak force while decreasing fibrosis and myofiber size [46].…”
Section: Key Pointsmentioning
confidence: 99%